CO2 Utilization and Long-Term Storage in Useful Mineral Products by Carbonation of Alkaline Feedstocks - Baciocchi, Renato; Costa, Giulia (Frontiers in Energy Research, 2021)
Accelerated carbonation is a carbon utilization option which allows the manufacturing of useful products, employing CO2-concentrated or -diluted emission sources and waste streams such as industrial or other processing solid residues, in a circular economy perspective. If properly implemented, it may reduce the exploitation of virgin raw materials and their associated environmental footprint and permanently store CO2 in the form of Ca and/or Mg carbonates, thus effectively contributing to climate change mitigation. In this perspective article, we first report an overview of the main mineral carbonation pathways that have been developed up to now, focusing on those which were specifically designed to obtain useful products, starting from different alkaline feedstocks. Based on the current state of the art, we then discuss the main critical issues that still need to be addressed in order to improve the overall feasibility of mineral carbonation as a CCUS option, as well as research needs and opportunities.